(untitled) (American Journal of Technology and Applied Sciences, 2023)
The COVID-19 pandemic has caused profound structural changes in international tourism, influencing not only the volume of tourist flows but also traveler behavior patterns. The purpose of this article is to analyze the post-pandemic transformation of international tourist behavior and identify its key areas and management implications. The study utilizes an analytical review method based on a synthesis of scientific publications and reports from international organizations (OECD, UN Tourism , World Tourism Organization). Bank , WEF). It is shown that in the post-pandemic period, the role of risk and safety perceptions has increased, the demand for flexibility in planning and booking has grown, the structure of tourist motivations has shifted toward natural and "slow" forms of tourism, and digital tourism behavior has become more entrenched. It is demonstrated that the identified changes are sustainable and are shaping new requirements for international tourism management, implying a transition to a more flexible, resilient, and data -driven model for industry development.